Heart rate/running speed relationship during races and non-competitve conditions - Lambert, M. (2002)
The technology associated with measuring heart rate has developed so that heart rate can be measured accurately under free-living conditions and the data can be stored for later analysis. However, the interpretation of the heart rate measured during exercise is not as advanced. In accordance with this heart rate monitors are currently not being used to their full potential. It is known that under most conditions there is a linear relationship between workload and heart rate. Factors such as training status, duration of exercise, time of day, environmental conditions, state of hydration and emotional arousal can affect this relationship. Providing these factors are controlled the measurement of the heart rate/workload relationship is remarkably constant and can be used as a marker of exercise intensity. Furthermore, changes in this heart rate/workload relationship over a training season can be used as a marker of training status. This presentation will discuss evidence-based research that focuses on the reliability of measuring heart rate during training and competition. The overall goal of the symposium is to present data that will contribute to a better and more accurate interpretation of heart rate measured during exercise and competition. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)